HUBUNGAN KEBIASAAN BELAJAR MENGGUNAKAN MEDIA YOU TUBE DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PAI (Studi Survei Pada Mata Pellajaran PAI di SMAN 1 Tambun Selatan) - Faishol Aziz Billah; Yayat Suharyat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2020)
The formulation of the research problem is Is there a relationship learning habits using youtubemedia with student achievement in PAI subjects at SMAN 1 Tambun Selatan. This study aims todetermine and analyze the relationship between learning habits using youtube media with studentachievement at SMAN 1 Tambun Selatan. The population in this study were all students of class XI asmany as 385 students. While the sample of this study were 79 students.The population taken from thisstudy used the Slovin formula. Before testing the data analysis, the lowest and highest values, mean,median and mode of the two variables were searched. In the known variable Xthe lowest value is 44and the highest value is 67, which results in a mean / mean value of 53.81, with a median value of54.00, and the most frequently occurring value / mode is 53. In the variable Y, the lowest value is 81and the highest value is 92, which yields a mean/mean value of 85.99, with a median/median value of86.00, and the most frequently occurring value/mode is 85. In testing the normality of the X variablewith the help of the SPSS 20 application, the value of 0.929 0.05 (normally distributed). And in thehomogeneous test produces the value of0.057 0.05(homogeneous data). The results of this study canbe seen in the correlation test and simple linear regression test. Correlation test get data0.001 0.05which means the data is correlated. In the regression test ,. Dith Pearson Correlation value 0.374, (R²)of 0.140 or 14% affects student achievement.